Sheikh Nawawi Al-Jawi’s Sufism Thoughts of The Book Marăqil ‘Ubūdyah - Subaidi; Slamet Untung; Siti Marpuah; Rahimah Embong; Siti Rosilawati Ramlan (Faculty of Ushuluddin, Adab and Dakwah UIN K.H. Ab, 2024)
Non-Indexed Publication